A cross-sectional study of factors associated with life satisfaction in Thai elderly - S. Joowong; B. Junsirimongkol; P. Khaektao; T. Doungyota; K. Paomee (European Psychiatry, 2022)
Introduction Aging raises wide-ranging issues within social, economic, welfare, and health care systems. Life satisfaction is regarded as an indicator of the quality of life which, in turn, is associated with mortality and morbidity in older adults.